2018
DOI: 10.1080/03004430.2018.1439940
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of parent-teacher communication during infant transition to childcare in Portugal

Abstract: Although literature reports associations between parent-teacher communication and childcare quality, little is known about how such communications are related to family, child and childcare characteristics. This study examines whether child, family and childcare experience characteristics predict the level of parent-teacher communication, and differences between parents' and teachers' reports of communication. Participants were mothers of 90 infants and their teachers in childcare in Portugal. Results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
(93 reference statements)
0
7
0
3
Order By: Relevance
“…Os grandes eixos de publicações do projeto tratam da relação família-creche, do bem-estar dos bebês e da implementação de estratégias de transição (e.g. Coelho et al, 2018).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Os grandes eixos de publicações do projeto tratam da relação família-creche, do bem-estar dos bebês e da implementação de estratégias de transição (e.g. Coelho et al, 2018).…”
Section: Resultsunclassified
“…Um dos focos das investigações se referia às pessoas e aos aspectos das relações envolvidos na transição. Nesse sentido, foi entendida como facilitadora uma relação entre pais e professores, em que tivesse se dado o estabelecimento de comunicação sobre acontecimentos, hábitos e comportamentos relacionados ao bebê (Coelho et al, 2018;Grande, Nunes, Coelho, Cadima, & Barros, 2017).…”
Section: Quanto Tempo Dura O Processo De Transição Com O Ingresso Na ...unclassified
“…It is observed that transition can benefit from a broader diversification of practices conducted by several authors and institutions, and that the institution-family partnership is essential so that these discrepancies can be understood based on the respective contexts that constitute specific habits of the infant (Coelho et al, 2015;Peixoto et al, 2017). Therefore, it is also important to maintain the communication between families and teachers when it comes to contrasting rhythms throughout transition, so that the temporal flow of the infant who transits across these contexts can be embraced and treated in a more integrated and shared manner (Grande et al, 2017;Coelho et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Even though staff express confidence, it is possible organisational and practical issues get in the way of opportunities for parent–educator communication. Coelho et al (2019) cited factors such as the limited time for communication at drop off and pick up times as both educators and parents feel rushed during these periods. An Australian case study also pointed to a discrepancy between skills and application with no evidence of a true partnership despite identified performance standards being met (Rouse & O’Brien, 2017).…”
Section: Discussionmentioning
confidence: 99%